2019
DOI: 10.11622/smedj.2019038
|View full text |Cite
|
Sign up to set email alerts
|

Lateral versus central tendon-splitting approach to insertional Achilles tendinopathy: a retrospective study

Abstract: This study aimed to compare operative outcomes between the lateral approach (LA) and the central approach (CA) to insertional Achilles tendinopathy (IAT). METHODS We retrospectively reviewed patients who underwent surgical treatment for IAT using the LA or CA. Patients' demographic data, postoperative complications and satisfaction rate were reviewed. Clinical outcomes were prospectively assessed preoperatively, at three months postoperatively and at the last visit, including patients' visual analogue scale (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The lateral approach provided better pain relief at 3 months, but there was no difference in function or pain at the time of final follow-up. The central-approach group had 5 patients with delayed wound-healing, significantly more than the 1 in the lateral-approach group (p = 0.049) 41 . The authors also reported no significant difference in sural nerve injury and credited the lack of nerve injury in the lateral approach to meticulous handling of soft tissue.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The lateral approach provided better pain relief at 3 months, but there was no difference in function or pain at the time of final follow-up. The central-approach group had 5 patients with delayed wound-healing, significantly more than the 1 in the lateral-approach group (p = 0.049) 41 . The authors also reported no significant difference in sural nerve injury and credited the lack of nerve injury in the lateral approach to meticulous handling of soft tissue.…”
Section: Resultsmentioning
confidence: 91%
“…(p 5 0.049) 41 . The authors also reported no significant difference in sural nerve injury and credited the lack of nerve injury in the lateral approach to meticulous handling of soft tissue.…”
Section: Continuedmentioning
confidence: 97%
“…Lin et al (28) concluded that calcaneoplasty and reattachment of the Achilles tendon via a lateral approach for insertional tendinopathy enable early weight-bearing and achieve a good outcome and pain relief. Xia et al (29) reported the lateral approach provided better short-term pain relief and reduced delayed wound healing compared with the central approach, while other outcomes were comparable. In our series of 14 patients who underwent tendon detachment, debridement, and reattachment for IAT and were followed up for a mean of 14 months, the mean AOFAS ankle-hindfoot score improved from 67 to 90, the mean VAS score declined from 4.82 to 1.21, and the VISA-A score improved from 62 to 82.…”
Section: Discussionmentioning
confidence: 99%
“…40,58,60,61,63,68,74,75,79,86,87,89,93,96,102,110,119,122,125,[132][133][134]138,142,[145][146][147][148]150,151,[153][154][155][158][159][160]165,166,169,171,173,181,185,186,188,189,193,198,204,212,223,226,…”
mentioning
confidence: 99%